ANDRAGOGICAL MODEL OF PREPARATION OF CLASS TEACHERS FOR THE FORMATION OF SOCIAL COMPETENCE OF ADOLESCENTS - Hrynchenko Н.В. (Pedagogy of Higher and Secondary Education, 2022)
The article presents the author’s andrological model of the development of motivational, cognitive, and creative sphere of class teachers in relation to (with respect to) organization and planning of extracurricular work during formation of social competent teenager’s personality.